2010
DOI: 10.17489/biohun/2010/1/07
|View full text |Cite
|
Sign up to set email alerts
|

Force measurement of hand and fingers

Abstract: Objective: To determine forces of hand and fi ngers in model situations.Methods: Subjects were 16 university students (males). Dyna-8 force measuring system was used, which is equipped with transducers making the measurement of handgrip strength and forces of fi ngers possible. The maximum force value is displayed digitally and simultaneously, the complete force diagram is shown on the computer monitor.Results: Right and left hand strengths and forces of all fi ngers were recorded, and descriptive statistics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The pressure was controlled so that the rolling action did not damage the substrate. The pressure was not measured during the process, although it has been observed that middle and index fingers typically exert forces ranging between 35-50 N 26 . This was carried out when isopropanol was no longer observed on the surfaces and was carried out in order to promote embedding of the nanoparticles into the plastic.…”
Section: Synthesis Of the Carboxylate Functionalized Al2o3 Nanoparticlesmentioning
confidence: 99%
“…The pressure was controlled so that the rolling action did not damage the substrate. The pressure was not measured during the process, although it has been observed that middle and index fingers typically exert forces ranging between 35-50 N 26 . This was carried out when isopropanol was no longer observed on the surfaces and was carried out in order to promote embedding of the nanoparticles into the plastic.…”
Section: Synthesis Of the Carboxylate Functionalized Al2o3 Nanoparticlesmentioning
confidence: 99%
“…In the current study, the Taco test was simulated via a linearly increasing pressure of 200 Pa [ 44 ] applied on the external surface of the lens while the lens nodes on Y-axis were fixed. As a result, the soft lens bends, and stresses build on the lens surface.…”
Section: Methodsmentioning
confidence: 99%
“…Bretz 23 , et al has also performed some study to measure the fingers forces. Table 11 shows the results.…”
Section: Force and Torquementioning
confidence: 99%